Lipidomics Analysis of the Lipid Composition of Three Tissues of Cyperus esculentus L. during Three Growth Stages Based on Ultra-high Performance Liquid Chromatography-Mass Spectrometry - YANG Yaxuan, BIAN Miaomiao, LIU Yanqing, LIU Jun, XING Jun, TU Yixian (Shipin Kexue)
In order to investigate changes in the lipid composition of different tissues of Cyperus esculentus L. at different growth stages, non-targeted lipidomics based on ultra-high performance liquid chromatography-mass spectrometry (UPLC-MS) was employed for relative quantitative analysis of the lipid metabolites in the above-ground stems, tubers, and roots of C. esculentus L. after 70, 93, and 120 days of growth. A total of 16 904 lipid metabolites were identified and 720 differential lipid metabolites were found between the three tissues, the contents of differential lipid metabolites being significantly higher in the tubers than in the above-ground stems and roots. The main lipids accumulated in the growth process of C. esculentus L. were triacylglycerols (TAG). All three tissues had high proportions (higher than 57.3%) of unsaturated fatty acids relative to the total fatty acids (FAs), and the relative contents of unsaturated fatty acid FA(18:1) and FA(18:2) in the tubers were also high. This study provides basic data and a scientific basis for the application of C. esculentus L. in various fields such as food processing and product development.